Characteristics of Subpacket Structures in Ground EMIC Wave Observations - Kakad, Bharati; Omura, Yoshiharu; Kakad, Amar; Upadhyay, Aditi; Sinha, Ashwini K. (My University, 2018)
Recent studies using satellite observations have reported that subpacket structures play an important role in determining the characteristics of electromagnetic ion cyclotron (EMIC) rising/falling tone emissions. The purpose of the present study is to investigate the subpacket structure characteristics in the ground observations of the EMIC waves. It will help us understand the effect of propagation on the EMIC subpacket structures. The induction coil magnetometer observations from Maitri, Antarctica (Geog. 70.77∘S, 11.75∘E, Geomag. 63.11∘S, 53.59∘E, L = 5), are used. Six quiet time EMIC events during 2015–2016 are analyzed and their details are presented. Based on their frequency extent in the power spectrum, four (two) events are speculated to be linked with proton (helium) band EMIC waves. For these events, the EMIC rising tone occurrence periods are estimated to be 1.9–6.7 min. Our analysis suggests that the amplitude-frequency dependence of EMIC subpacket structures is less significantly affected during their prorogation to the ground. Overall, it is found that more than 70% of the time the EMIC waves are right-handed elliptical polarized. An interesting feature is that the duration of the subpacket structure is found to be directly proportional to the EMIC wave amplitude. The observed characteristics and tendencies followed by EMIC subpacket structures on the ground are examined in the light of existing nonlinear wave theory and they are in good agreement. The EMIC wave amplitudes on the ground are found to be 16–80 times lower than the expected theoretical estimates of the wave amplitudes in the source region.
Keywords: Electromagnetic ion cyclotron; EMIC Wave